Acoustophoretic Orientation of Red Blood Cells for Diagnosis of Red Cell Health and Pathology. Issue 1 (December 2018) - Rico, Laura; Juncà, Jordi; Ward, Mike; Bradford, Jolene; Bardina, Jorge; Petriz, Jordi
Abstract Distortions of the normal bi-concave disc shape for red blood cells (RBCs) appear in a number of pathologies resulting from defects in cell membrane skeletal architecture, erythrocyte ageing, and mechanical damage. We present here the potential of acoustic cytometry for developing new approaches to light-scattering based evaluation of red blood cell disorders and of the effects of storage and ageing on changes or damage to RBCs membranes. These approaches could be used to immediately evaluate the quality of erythrocytes prior to blood donation and following transfusion. They could also be applied to studying RBC health in diseases and other pathologies, such as artificial heart valve hemolysis, thermal damage or osmotic fragility. Abnormal distributions of erythrocytes can typically be detected after just 30 to 45 seconds of acquisition time using 1–2 µL starting blood volumes.